Social Cultural Characteristics of Farmers and Types of Plant Cultivated on Local Native Forage Sources in Kupang Regency - Edi Djoko Sulistijo; Upik Syamsiar Rosnah (Buletin Peternakan, 2022)
The local native forage sources in Kupang Regency have their own specifications due to different management. This research is aimed at describing socio- cultural characteristics of farmers and the types of plant cultivated on local native forage sources planted in the farms in Kupang Regency. It was conducted in Oeletsala Village, Taebenu Sub-District, Kupang Regency from August 2015 to April 2017. The research method was survey, direct observation and measurement in the field as well as secondary data collection. The data were analyzed descriptively in the form of averages, tables and graphs. The results showed that amarasi farm were more widely distributed than dry mamar and selobua. Most of the farmers were at their productive age, have elementary school education, and 1-4 family members. The background of farming and the reasons for choosing the type of farms were varied. Likewise, the types of plants were also varied. Utilization of the types of plants have experienced a shift from conservation goals to multi-function. In amarasi, dry mamar and selobua farm were found 62, 77 and 53 types of plants. Forage which is commonly used at the farmer level were 13 species dominated by Leucaena leucocephala. While, 23 other commodities were not forage and they were harvested in certain seasons and for household needs. In conclusion, the farmers were at their productive age, with low education, and small family size. The background of establishing the farms and the reasons for choosing the type of farms varied. The types of plants have been shifted from conservation goals to being multi-purposes. The types of plants that were widely developed other than forage are dominated by food crops and horticulture. The three types farms can have a positive impact on feed and food security, source of farmer’s income and land conservation